OXYMORPHONE INDUCED THROMBOTIC MICROANGIOPATHY MIMICKING ATYPICAL HEMOLYTIC UREMIC SYNDROME - Gandhi, Amibhen; Ullah, Saad; Kotadia, Shani; Nasser, Samer (Journal of Ayub Medical College Abbottabad, 2017)
Background: Atypical Haemolytic Uremic Syndrome (aHUS) is a rare life threatening entity characterized by thrombocytopenia, haemolytic anaemia and renal dysfunction. It is a thrombotic microangiopathy related to genetic mutations in the alternate complement pathway and has a distinct pathophysiology which makes it harder to distinguish from other microangiopathies. We present a case of a 25-year-old male patient with history of polysubstance abuse who presented with chest pain and dyspnoea. He admitted to using injectable oxymorphone (Opana) two weeks before presentation. Patient’s vital signs were stable except for tachycardia and high blood pressure. On physical examination, epigastric tenderness and mild splenomegaly was appreciated. Urine Drug Screen was positive for oxycodone and opiates. Laboratory work up revealed haemolytic anaemia, thrombocytopenia and acute kidney injury. Extensive evaluation resulted in our impression of the disease being atypical haemolytic-uremic syndrome. He was managed with dialysis, intravenous steroids and plasmapheresis with improvement in his hematologic parameters. Keywords: Acute renal failure; atypical Haemolytic uremic syndrome; Opana; oxymorphone use; endothelial dysfunction; drug abuse